MCSE guide to designing - Kezema, Conan (Course Technology, 2002)
Designed to provide students and network administrators with the knowledge they need to design and implement an effective security strategy in a network environment, this guide book prepares individuals for the MCSE certification exam #70-220 Designing Security for a Windows Microsoft 2000 Network